Improving Self Confidence in Children through Role Play at An-Nida Cinere Paud - Asmarany; Nita Priyanti; Lia Kurniawaty (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the strategies and concrete evidence of role-playing activities that can help improve children's self-esteem at PAUD An-Nida. The method used is classroom action research with a focus on role-playing activities in developing children's self-esteem. Through role-playing, children can develop social skills, empathy, creativity, and communication skills, all of which contribute to increasing self-esteem and role-playing skills have a significant role in improving children's self-esteem at PAUD An-Nida. This helps them build strong self-confidence and strengthen their social relationships. By focusing on the development of children's psychological and social aspects, PAUD An-Nida makes a major contribution to shaping a future generation that is confident, empathetic, and emotionally intelligent.